PENGAMATAN LANGSUNG TERHADAP KELENGKAPAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD PASAR MINGGU - Abdul Rahman La Ede; Muhammad Hadi; Rohadi Haryanto (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2022)
Nursing documentation is everything written and printed related on the development of patient's health status. Nursing documentation should comprehensive and flexible in which fixed, maintained the quality and care continuity. The aim of this research was to know correlation the supervise clinic managing toward documentation completeness ASKEP based IT at hospital ward RSUD Pasar Minggu South of Jakarta,2019. This study used cross sectional. The sample of the study were 117 respondent which used two proporsion different test. The instrument of this study used valid and realible questionnaire. For testing Bivariat used Chi-square test while multivariat testing used double logistic regration. the result of this study of direct observation was p-value 0.005 < 0.05 which indicated that there was any significant correlation toward documentation completeness ASKEP based IT with Odd Ratio 10,352. The clinic supervice and direct observation have correlation toward documentation completeness ASKEP based IT, it was suggested and expected that RSUD Pasar Minggu can maintain and develop the quality that already exists.